Experiences of people with learning disabilities in the criminal justice system. (30th October 2013) - Hyun, Elly; Hahn, Lyndsey; McConnell, David
<x xml:space="preserve">Abstract</x> Accessible Summary Many people with learning disabilities are caught up in the criminal justice system. Yet few studies have explored what this is like for them. The available research suggests that people with learning disabilities often feel alone and afraid when they are caught up in the criminal justice system. They do not understand what is happening to them, and they feel like there is no one they can turn to for support. The findings raise concerns about how people with learning disabilities are treated within the criminal justice system, and whether their rights are being respected. Further research is needed to better understand the experiences and support needs of people with learning disabilities who are caught up in the criminal justice system. Summary The aim of this review is to synthesise findings from research about the experiences of people with learning disabilities who have faced arrest and jail time. After an extensive search of the literature, four relevant articles were found. The first‐person accounts presented in these four studies were pooled, and a thematic analysis was undertaken. Three common themes were identified: (i) study participants did not understand what was happening to them, or why, (ii) they felt alone, and they did not know where to turn, or to whom for support and (iii) they were uncertain about what to say or do. Overall, the findings raise concerns about the treatment of people with learning disabilities in the criminal justice system and their access to procedural justice. Further research is needed to improve understanding of their experiences and support needs. There is unequivocal evidence that persons with learning disabilities are over‐represented in the prison population. To date however, few studies have investigated their first‐hand experience, including their experiences of being interrogated, of standing trial, serving time and transitioning back into the community. The purpose of this review is to draw what insights we can from the limited available data and to identify directions for future research.